Rencana Strategis Sekretariat Daerah Kota Sawahlunto: Upaya Peningkatan Kinerja dan Pelayanan Publik - Fauzan Delesa; Syafwandi (PT. Hasba Edukasi Mandiri, 2025)
The strategic planning of the Regional Secretariat of Sawahlunto City is a crucial factor in enhancing the effectiveness and efficiency of regional governance. This study aims to formulate a comprehensive strategic plan using SWOT analysis and stakeholder mapping, alongside the Analytic Hierarchy Process (AHP) to prioritize the most suitable strategies. Data were collected through in-depth interviews with relevant officials, questionnaires to staff and stakeholders, and documentation of regulations and performance reports. The findings indicate that the Regional Secretariat needs to strengthen human resource capacity, improve standard operating procedures (SOP), and enhance cross-agency collaboration. The implementation of these strategies is expected to improve public service quality and strengthen the governance of Sawahlunto City. This study offers practical policy recommendations and serves as an academic reference for strategic planning at the local government level.